Islamic Work Ethics and Service Quality on Banking Performance at Bank Sumut Syariah Medan Branch - Rida Nursani Btr (Penerbit Jurnal Indonesia, 2022)
Performance is the lifeblood of a company that must get attention to maintain the existence and resilience of the company in competitiveness with other companies. This research aims to reveal, (1) the influence of work ethics on performance banking, (2) the influence of Islamic service quality on banking performance, and (3) the influence of work ethics and Islamic service quality at PT. Bank Sumut Syariah Medan Branch. The approach used is descriptive quantitative. The sampling technique used was purposive sampling. The number of samples is 20 employees spread over at Bank Sumut Syariah Medan Branch. The results of the study prove (1) the results of the t-test scores on work ethics on banking performance has a sig value of 0.017 <0.05 then the work ethic has an effect on the banking performance of North Sumatra Syariah Medan Branch. (2) The results of the t-test value on the quality of Islamic services to banking performance has a sig value of 0.028 > 0.05 which means that the quality of service Islam affects the banking performance of the North Sumatra Syariah Medan Branch. (3) The results of the F test sig of 0.000 < 0.005 so that based on the value of the significance of work ethic and service quality simultaneously in PT. Bank Sumut Syariah Medan Branch.